2011
DOI: 10.1108/14720701111108817
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐businesses need support: survival precedes sustainability

Abstract: Purpose -The purpose of this paper is to establish the role of micro-businesses in providing a sustainable business and community environment, and to share the perceptions of micro-business operators about the support they need to survive and be successful.Design/methodology/approach -An examination of literature regarding survival and available support for small businesses is followed by results from a New Zealand-based empirical study of micro-business operators.Findings -Micro-businesses are the dominant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is therefore important that micro enterprises have access to knowledge sharing and innovation as entrepreneurial orientation alone would not help these businesses to perform. It is important for business owners to get support from community-based networks (Samujh, 2011) as these networks can be the basis for knowledge sharing and innovation. As also suggested by previous findings, knowledge sharing within the company would facilitate a better understanding of business objectives; therefore, tasks could be done better, resulting in better business performance (O'Dell & Hubert,2011;Amir & Parvar, 2014;Wing et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important that micro enterprises have access to knowledge sharing and innovation as entrepreneurial orientation alone would not help these businesses to perform. It is important for business owners to get support from community-based networks (Samujh, 2011) as these networks can be the basis for knowledge sharing and innovation. As also suggested by previous findings, knowledge sharing within the company would facilitate a better understanding of business objectives; therefore, tasks could be done better, resulting in better business performance (O'Dell & Hubert,2011;Amir & Parvar, 2014;Wing et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that about 78.7% of business establishments in Malaysia were dominated by MEs (SME Annual Report 2014). Therefore, they play an important role in maintaining a stable and sustainable business environment (Samujh, 2011). A study done by Jamak et al (2011) on micro enterprises revealed that most micro enterprises failed due to lack of motivation, marketing approaches, management and marketing as well as competitive capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…advice during mergers and acquisitions and tax-related advice) and nonbusiness advice (e.g. advice on private wealth matters such as the design of a will and other nonfinancial objectives) (Blackburn et al , 2018; Samujh, 2011; Stone, 2015). While some studies argue that accountants are not always included in managerial decision-making (Blackburn et al , 2018), especially when dealing with SME owners with predominantly nonfinancial goals (Stone and Lightbody, 2012), others show an increasing pressure for accountants to advise their SMEs (Ma et al , 2021).…”
Section: Findings and Analysismentioning
confidence: 99%
“…A major criticism was the "top down" approach using a framework that is biased towards large and/or listed companies (Devi and Samujh, 2014;Di Pietra et al, 2008;Evans et al, 2005;Perera et al, 2022). Unlike large entities, SMEs are more likely to focus on survival than on growth and profit maximisation (Hasle et al, 2012;Samujh, 2011;Wijekoon et al, 2022). Additionally, the separation of ownership and control is not common in the majority of SMEs (Carsberg et al, 1985;Sassi and Damak-Ayadi, 2022) and most of them are formed and operated as family businesses (Fox et al, 1996;Motwani et al, 2006;Tatoglu et al, 2008;Wijekoon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%